Polarization‐Dependent Photoluminescence of a Highly (100)‐Oriented Perovskite Film. Issue 3 (9th January 2020) - Yun, Sangeun; Kim, Taehee; Choi, Yung Ji; Lee, Sang Hyeon; Kim, Hae‐Jin; Kim, Dongho
Abstract: Lead halide perovskite is one of the attractive functional materials owing to its outstanding opto‐electronic properties, which have been addressed in numerous studies. This study aims to clarify the link between the growth pattern and the charge carrier related properties for the highly oriented perovskite film along the [100] direction. For this purpose, a CH3 NH3 PbI3 thin film mainly grown along the [100] direction was fabricated and subjected to spectroscopic analysis to understand the basic optoelectronic features of the oriented film. A perovskite film with random growth was also fabricated for comparison. In particular, results from excitation polarization photoluminescence spectroscopy (ExPPS) revealed that the orientation of transition dipole moment, which is relevant to the anisotropic property of the film, is attributed to the growth direction of the perovskite film. This study suggests that the absorption anisotropy can affect the anisotropy in properties of the perovskite device. Furthermore, photodetectors with the perovskite films were fabricated to investigate the effect of growth direction on the photodetector performances, revealing that a photodetector with the oriented perovskite film showed larger photoresponses. In order to provide an explanation for such result, we performed a PL lifetime imaging study of the oriented and randomly grown perovskite films. Abstract : Better through orientation ? The anisotropic absorption of the oriented perovskite film along the [100] direction was investigated by providing information about the spatial orientation of the transition dipole moments of perovskite.